Köbner and Pastia Signs in Acute Hemorrhagic Edema of Young Children: Systematic Literature Review - Gabriel Bronz; Danilo Consolascio; Mario G. Bianchetti; Pietro O. Rinoldi; Céline Betti; Sebastiano A. G. Lava; Gregorio P. Milani (MDPI AG, 2022)
Acute hemorrhagic edema of young children, a benign skin-limited vasculitis, predominantly affects children 2 years of age or younger. The prevalence and clinical features of the Köbner and Pastia signs have never been systematically investigated in this vasculitis. To address this issue, we analyzed the data contained in the Acute Hemorrhagic Edema Bibliographic Database, which incorporates all reports on hemorrhagic edema published after 1969. A total of 339 cases (236 males and 103 females; 11 (8-18) months of age; median and interquartile range) were documented with at least 1 photograph and therefore included in this analysis. The Köbner sign occurred in 24 cases (14 males and 10 females; 11 (7-17) months of age), the Pastia sign in 51 cases (39 males and 12 females; 11 (8-15) months of age), and both Köbner and Pastia signs in 8 cases (7 males and 1 female; 11 (7-17) months of age). The lower legs, thighs, waistline, and groin were the regions that were most commonly affected with the Köbner sign, while the ankle, feet, cubital fossa, and elbow were most affected with the Pastia sign. The Köbner and Pastia signs are clinically relevant; they occur in about every fourth child affected with hemorrhagic edema and do not influence the disease progression.